2020
DOI: 10.1159/000509775
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hearing Impairment in Primary Congenital Hypothyroidism

Abstract: <b><i>Background:</i></b> An association between hearing impairment (HI) and congenital hypothyroidism (CH) has been reported previously. However, in general, studies were retrospective and had small sample sizes, and the results were variable and inconclusive. The aim of our study was to assess the prevalence of HI among patients with CH and to examine factors potentially predictive of HI including severity of CH, etiology of CH, and timing of treatment initiation. <b><i>Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Four patients had sensorineural hearing impairment. A high rate of hearing impairment in CH has been shown recently by our group [24]. Furthermore, TPO mutations have been reported to be associated with sensorineural deafness in humans [25] as well as in animal models [26], indicating that the TPO enzyme itself may have a role in the development of the auditory system.…”
Section: Discussionmentioning
confidence: 76%
“…Four patients had sensorineural hearing impairment. A high rate of hearing impairment in CH has been shown recently by our group [24]. Furthermore, TPO mutations have been reported to be associated with sensorineural deafness in humans [25] as well as in animal models [26], indicating that the TPO enzyme itself may have a role in the development of the auditory system.…”
Section: Discussionmentioning
confidence: 76%
“…2,14 This further highlight the importance of timely treatment in children with congenital hypothyroidism, especially considering that the severity of congenital hypothyroidism and the child's age at treatment initiation is directly associated with the degree of hearing loss. 15 In our presented case, the patient first referred to us at the age of 6 months where growth and developmental disorders had occurred. As the patient's auditory organs had been damaged, it became difficult to rehabilitate the patient's hearing ability.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, some studies detailed subtypes of CH including athyreosis, dysgenesis, ectopic thyroid, dyshormonogenesis, and transient CH. While some studies reported no association between hearing impairment and CH etiology (Vanderschueren-Lodeweyckx et al 1983;Almagor et al 2020), other studies observed more severe HL in their children with athyreosis compared to ectopic thyroid (Lichtenberger-Geslin et al 2013;Bruno et al 2015). Bruno et al (2015) noted an association between children with severe CH (defined by CH etiology including athyreosis, TSH levels, and age at bone maturation delay) and greater degrees of HL as assessed by PTA.…”
Section: Studies Reporting On Thyroid Disorder Subtypes and Thyroid H...mentioning
confidence: 99%
“…Following widespread screening, intellectual disability due to CH decreased significantly; however, the effect of early screening and treatment on hearing outcomes in children has been less dramatic. Reports of HL prevalence range from 20% to 47% (Vanderschueren-Lodeweyckx et al 1983; Rovet et al 1996; Almagor et al 2020) in cohort studies and the effect of LT4 therapy on hearing improvement is not well-established based on the few longitudinal studies that have followed children into adolescence (Léger et al 2011; Lichtenberger-Geslin et al 2013). Even in older children with CH and normal-hearing thresholds, subclinical hearing disorders could be present.…”
Section: Introductionmentioning
confidence: 99%